Manajemen Operasional Dan Al-Qur’an - Muhammad za’im musyaffa’ (https://ejournal.insuriponorogo.ac.id/, 2023)
Operational management is a very important activity in the company because it includes a whole range of activities ranging from planning, production to marketing strategies. With operational management, the company is able to maximize starting from human resources, production resources, to operational activities of similar companies in order to produce products at a low cost but in accordance with the wishes and needs of consumers. This study aims to prove whether there is a link between management science, especially operational management by using secondary qualitative research methods because it uses ready-made data sources, namely the Qur'an and books that discuss management. The results of this study prove that there is a link between the verses of the Qur'an with operational management so that it can be concluded that the values contained in the science of operational management is directly proportional to what is described in the Qur'an.